Buying Intention And Factors Influencing Buying Behavior - Migoko, Halima Abdallah; Vaicondam, Yamunah (International Journal of Engineering and Technology, 2018)
This study attempts to determine the factors that influenced passengers’ airline selection for domestic airlines in Tanzania. This is because of persistent rise and decline of some airlines companies in Tanzania. The objectives of this study is to examine factors influencing the buying intention of airlines passengers’ selection, to examine the relationship between buying intention and buying behavior of airlines passengers in Tanzania and to investigate the mediating effect of buying intention on the relationship between factors influencing and buying behavior. This study employed quantitative method based on questionnaire survey. The targeted population for this study was airlines passengers departing and landing at Julius Nyerere International Airport and sample size of this study is 367. Data was collected using closed ended questionnaire and analyzed using SPSS. The analyzed findings depicted that social acceptability; service quality and airline reputation had significant effect on the factors influencing airline passenger’s selection. It also revealed that price, service quality; social acceptability, airline reputation and frequent flier, could be used to predict buying intention, where this influence the buying behavior of airline passengers for chosen flights. This implies that airline managers need to be adoptive by improving passengers’ expectation through providing quality service, based on the result overall of the respondents consider other factors than price and frequent flier which influences their buying behavior. Most of them value how societies accept airlines companies, service quality and goodwill of the companies in the market.